Charge density studies of single and transient (single to double) boron–oxygen bonds in (NH4)2B4O5(OH)4·2H2O. Issue 39 (27th September 2022) - Gajda, Roman; Piekara, Anna; Tchoń, Daniel; Woźniak, Krzysztof; Sławiński, Wojciech A.
Abstract : A H4 B4 O9 2− ion which makes up the (NH4 )2 B4 O5 (OH)4 ·2H2 O crystal structure has two types of boron–oxygen bonds, i.e. single B–O bonds and an intermediate between single and double BO bonds. Abstract : A H4 B4 O9 2− ion which makes up the (NH4 )2 B4 O5 (OH)4 ·2H2 O crystal structure has two types of boron–oxygen bonds, i.e. single B–O bonds and an intermediate between single and double BO bonds. Differences between these two bond types are visible not only because they differ by their lengths but also a topology of electron density distribution differs. This also gives a hint as to how to distinguish between these two bond types. Experimental results based on multipole model refinement gave excellent agreement with theoretical calculations and literature data. Calculations at bond critical points for B–O and BO (electron density, the Laplacian of electron density and the localized-orbital locator function) suggest us how boron–oxygen bonds should be categorised with respect to compounds previously reported in the literature. Additionally, a novel synthesis method for the investigated compound has been developed, which involves crystallization from an aqueous solution of BH3 NH3 dissolved in a mixture of tetrahydrofuran and water.